2006
DOI: 10.1038/sj.onc.1209838
|View full text |Cite
|
Sign up to set email alerts
|

Loss of mammary epithelial prolactin receptor delays tumor formation by reducing cell proliferation in low-grade preinvasive lesions

Abstract: Top quartile serum prolactin levels confer a twofold increase in the relative risk of developing breast cancer. Prolactin exerts this effect at an ill defined point in the carcinogenic process, via mechanisms involving direct action via prolactin receptors within mammary epithelium and/or indirect action through regulation of other hormones such as estrogen and progesterone. We have addressed these questions by examining mammary carcinogenesis in transplants of mouse mammary epithelium expressing the SV40T onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 50 publications
2
58
0
Order By: Relevance
“…The evidence supporting a role for PRL-PRLR signaling in breast cancer is multifold. Directed expression of PRL in the mammary gland in mice induces a high frequency of mammary tumor development (12), whereas genetic knockout of the PRLR loci inhibits the growth of mammary tumors (13). In humans, PRLR protein and/or mRNA have been detected in the majority of breast tumors examined (7) and is overexpressed in malignant epithelium when compared with matched normal breast epithelium (14).…”
Section: Role Of Prl In Breast and Prostate Cancermentioning
confidence: 99%
“…The evidence supporting a role for PRL-PRLR signaling in breast cancer is multifold. Directed expression of PRL in the mammary gland in mice induces a high frequency of mammary tumor development (12), whereas genetic knockout of the PRLR loci inhibits the growth of mammary tumors (13). In humans, PRLR protein and/or mRNA have been detected in the majority of breast tumors examined (7) and is overexpressed in malignant epithelium when compared with matched normal breast epithelium (14).…”
Section: Role Of Prl In Breast and Prostate Cancermentioning
confidence: 99%
“…In another mouse breast cancer model system, Stat5a-null females exhibited delayed transforming growth factor-a-induced tumorigenesis (Humphreys & Hennighausen 2000). Third, a recent study by Oakes et al (2007) suggested that PRL receptor deficiency may prevent early progression of mammary gland neoplasia to invasive carcinoma. However, it is unclear so far whether this inhibition of mammary gland cancer progression would be due to the lack of JAK2/STAT5 signaling or inhibition of other PRL receptor-activated signal transduction pathways.…”
Section: Stat5a/b In Tumorigenesis Of Rodent Mammary Glandmentioning
confidence: 99%
“…In mice, transgenic over-expression of PRL induced formation of mammary tumours (Wennbo et al 1997), many of which were oestrogen receptor (ER)-positive (Rose-Hellekant et al 2003). PRLR knockout studies have shown a decrease of the mammary tumour growth rate (Oakes et al 2007). Based on the in vivo data, PRL was suggested to be a growth factor for cancer cells.…”
Section: Introductionmentioning
confidence: 99%